Multigroup Analysis: The Effect of Work From Home Policy Implementation on Apparatus Work Productivity - Setyarini, Trisna; Haris Wanto, Alfi; Eko Putra Sri Sentanu, I Gede (Sekolah Pascasarjana Universitas Brawijaya, 2023)
The COVID-19 pandemic has prompted the government to adopt a remote work system by issuing a WFH policy. This policy directly impacts changes in the government’s work system, which requires the apparatus to adapt quickly to maintain work productivity. By reviewing the implementation of WFH policies within the government, it will be known whether the policy impacts the work productivity of the apparatus. This study examines and analyzes the effect of WFH policy implementation on apparatus work productivity and whether there are differences based on gender, age, position, and education level. Data was collected through questionnaire surveys using Google form and analyzed with Multigroup Analysis using Smart PLS3. As a result, WFH policies that are implemented effectively in terms of communication, resources, employee disposition, and bureaucratic structure can increase the work productivity of the apparatus. Overall, there was no significant difference in the increased apparatus work productivity in implementing WFH based on gender, age, position, and education level. Keywords: work from home, policy implementation, apparatus work productivity, multigroup analysis